2021
DOI: 10.1210/jendso/bvab075
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between 24-hour LH and Testosterone Concentrations and With Other Pituitary Hormones in Healthy Older Men

Abstract: Objective To investigate the relationship between LH and T, which characteristics associate with the strength of this relationship, and their interrelationships with GH, TSH, cortisol, and ACTH. Design Hormones were measured in serum samples collected every 10 min during 24 h from 20 healthy men, comprising 10 offspring of long-lived families and 10 control subjects, with a mean (SD) age of 65.6 (5.3) years. We performed cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In their fundamental work, Schwartz et al [8] reported that the function of the anterior lobe of the pituitary gland probably relies on the integration of multiple received input signals, including hypothalamic, peripheral, and intrapituitary, which may have stimulatory or inhibitory effects on the hormone production. Interactions of somatotropic (GH) cells with other hormonal and non-hormonal pituitary cells in healthy elderly appear to be very important [9,10,11]. Pituitary folliculostellate cells (FS) can release various products into the intercellular space, and thus can influence the functioning of neighboring hormone-producing cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…In their fundamental work, Schwartz et al [8] reported that the function of the anterior lobe of the pituitary gland probably relies on the integration of multiple received input signals, including hypothalamic, peripheral, and intrapituitary, which may have stimulatory or inhibitory effects on the hormone production. Interactions of somatotropic (GH) cells with other hormonal and non-hormonal pituitary cells in healthy elderly appear to be very important [9,10,11]. Pituitary folliculostellate cells (FS) can release various products into the intercellular space, and thus can influence the functioning of neighboring hormone-producing cells [12].…”
Section: Introductionmentioning
confidence: 99%